Resilience in Wives with Homosexual Husband - Muhamad Fikri Maulana; A. Rachmad Djati Winarno; Sri Sumijati (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
Wives who find out their husbands are homosexuals often experience emotional surges such as disappointment, stress, depression and lead to meaninglessness of life, although in particular reason some are stood up from the sufferings. This study aims to determine the condition of resilience of wives whose husbands are homosexuals and the factors that influence them. Hope the results of the study will be useful for wives, families or households, especially in Indonesia, if they have problems with homosexual husbands. Some of them are able to develop resilience skills, at least they can be lesson for motivation and inspiration for wives, especially in Indonesia who are homosexuals in order to develop resilience skills. This research uses qualitative methods with a phenomenological approach. The participants of this study were two wives with homosexual husbands who lived in Central Java and Yogyakarta. Data collection was based on interviews and observations conducted directly at the participants' places, namely Jepara and Batang and through video calls. The results of this study showed that both participants were able to develop resilience after learning that their husband was homosexual. The stages are based on aspects such as emotional regulation, impulse control, optimism, causal analysis, empathy, self-efficacy and reaching out. Cultural factors, spirituality, social support and interpersonal communication skills were factors that influenced both participants in developing resilience so that they can go through the dark period of suffering to a life of light.